Microscopic Polyangiitis With Selective Involvement of Central and Peripheral Nervous System: A Case Report - Arienti, Federica; Franco, Giulia; Monfrini, Edoardo; Santaniello, Alessandro; Bresolin, Nereo; Saetti, Maria Cristina; Di Fonzo, Alessio (Frontiers in Neurology, 2020)
BACKGROUND: Microscopic polyangiitis is a necrotizing vasculitis that affects predominantly small-sized vessels in many organ systems. The disease generally causes glomerulonephritis, pulmonary damage, arthritis and neuropathy. An exclusive involvement of both central and peripheral nervous system is extremely rare. CASE PRESENTATION: A 62-year-old woman was admitted to our hospital with a 3-month history of right foot drop, recently complicated by intense myalgia, arthralgia and allodynia to tactile, vibratory and pressure stimuli. Since blood tests revealed elevated inflammatory indexes, we suspected either infectious or immuno-mediated disorders. Chest radiograph, blood culture series and echocardiogram revealed normal findings, while urinalysis showed a bacterial infection that was successfully treated. The neurophysiological findings were compatible with multiple mononeuritis and a brain MRI evidenced ischemic lesions of both basal ganglia and thalamus. A wide-spectrum auto-antibody assay revealed the presence of high titer perinuclear anti-neutrophil cytoplasmic antibodies specific for myeloperoxidase. According to these findings, the diagnosis of microscopic polyangiitis was made and the patient was successfully treated with IV methylprednisolone, followed by two doses of rituximab. CONCLUSIONS: An assessment of both central and peripheral nervous system should be included in the diagnostic evaluation of microscopic polyangiitis. The involvement of peripheral nervous system may arise the risk of relapsing course and treatment failure, therefore it should be considered in the choice of induction and maintenance therapy.